Genome analyses of 174 strains of Mycobacterium tuberculosis provide insight into the evolution of drug resistance and reveal potential drug targets. Issue 3 (22nd March 2021) - Verma, Helianthous; Nagar, Shekhar; Vohra, Shivani; Pandey, Shubhanshu; Lal, Devi; Negi, Ram Krishan; Lal, Rup; Rawat, Charu Dogra
Abstract : Mycobacterium tuberculosis is a known human pathogen that causes the airborne infectious disease tuberculosis (TB). Every year TB infects millions of people worldwide. The emergence of multi-drug resistant (MDR), extensively drug resistant (XDR) and totally drug resistant (TDR) M. tuberculosis strains against the first- and second-line anti-TB drugs has created an urgent need for the development and implementation of new drug strategies. In this study, the complete genomes of 174 strains of M. tuberculosis are analysed to understand the evolution of molecular drug target (MDT) genes. Phylogenomic placements of M. tuberculosis strains depicted close association and temporal clustering. Selection pressure analysis by deducing the ratio of non-synonymous to synonymous substitution rates ( dN/dS ) in 51 MDT genes of the 174 M . tuberculosis strains led to categorizing these genes into diversifying (D, dN/dS >0.70), moderately diversifying (MD, dN/dS =0.35–0.70) and stabilized (S, dN/dS <0.35) genes. The genes rpsL, gidB, pncA and ahpC were identified as diversifying, and Rv0488, kasA, ndh, ethR, ethA, embR and ddn were identified as stabilized genes. Furthermore, sequence similarity networks were drawn that supported these divisions. In the multiple sequence alignments of diversifying and stabilized proteins, previously reported resistance mutations were checked to predict sensitive and resistant strains of M. tuberculosis . Finally, to delineate the potential of stabilized or least diversified genes/proteins as anti-TB drug targets, protein–protein interactions of MDT proteins with human proteins were analysed. We predict that kasA ( dN/dS =0.29), a stabilized gene that encodes the most host-interacting protein, KasA, should serve as a potential drug target for the treatment of TB.